Mechanics of knee meniscus results from precise balance between material microstructure and synovial fluid viscosity - Camilo A. S. Afanador; Stéphane Urcun; Ivo F. Sbalzarini; Stéphane P. A. Bordas; Olga Barrera; Mohammad Mahdi Rajabi; Romain Seil; Anas Obeidat (PLoS ONE, 2025)
The meniscus plays a crucial role in the biomechanics of the knee, serving as load transmitter and reducing friction between joints. Understanding the biomechanics of the meniscus is essential to effective treatment of knee injuries and degenerative conditions. This study aims to elucidate the relationship between the porous microstructure of the human knee meniscus and its biomechanical function, specifically focusing on fluid dynamics at the pore scale. Here, we use two central-meniscus samples extracted from a human knee and reconstruct high-resolution geometry models from μ -CT scans. By eroding the channels of the original meniscus geometry, we simulate perturbed microstructures with varying porosities ( 53% to 80% ), whilst preserving the connectivity of the porous structure. We numerically solve for the fluid dynamics in the meniscus using a mesh-free particle method, considering various inlet pressure conditions, characterising the fluid flow within the microstructures. The results of the original microstructure associated with a physiological dynamic viscosity of synovial fluid are in accordance with biophysical experiments on menisci. Furthermore, the eroded microstructure with a 33% increase in porosity exhibited a remarkable 120% increase in flow velocity. This emphasises the sensitivity of meniscus physiology to the porous microstructure, showing that detailed computational models can explore physiological and pathological conditions, advancing further knee biomechanics research.